Celebrating Rose Watkins' 64th Birthday-207 Geneva Avenue - Watkins, Howard::::::::: (1983)
Stephanie Pin Woodward holding her son, Dottie Pin, Rose Watkins, Nancy Pin Coughlan holding baby daughter; two young daughters in middle